2015
DOI: 10.1111/mpp.12251
|View full text |Cite
|
Sign up to set email alerts
|

Effector discovery in the fungal wheat pathogen Zymoseptoria tritici

Abstract: Fungal plant pathogens, such as Zymoseptoria tritici (formerly known as Mycosphaerella graminicola), secrete repertoires of effectors to facilitate infection or trigger host defence mechanisms. The discovery and functional characterization of effectors provides valuable knowledge that can contribute to the design of new and effective disease management strategies. Here, we combined bioinformatics approaches with expression profiling during pathogenesis to identify candidate effectors of Z. tritici. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 84 publications
(127 reference statements)
2
60
0
Order By: Relevance
“…It is possible that the role of Avr3D1 is more pronounced under field conditions or at different developmental stages, for example in adult plants. An additional hypothesis to explain the apparent dispensability of Avr3D1 is that functional redundancy masks phenotypic effects in the knockout mutants (Marshall et al ., 2011; Win et al ., 2012; Mirzadi Gohari et al ., 2015; Rudd et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the role of Avr3D1 is more pronounced under field conditions or at different developmental stages, for example in adult plants. An additional hypothesis to explain the apparent dispensability of Avr3D1 is that functional redundancy masks phenotypic effects in the knockout mutants (Marshall et al ., 2011; Win et al ., 2012; Mirzadi Gohari et al ., 2015; Rudd et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Disruption of several of these effector candidate genes has shown that they are not essential for virulence. This may indicate functional redundancy or a major role in necrosis induction for other molecular players such as secondary metabolites, toxins and/or cell wall degrading enzymes (Gohari et al, 2015;Rudd et al, 2015). It was also suggested that programmed cell death is triggered by the pathogen at the onset of the necrotrophic phase (Keon et al, 2007).…”
Section: What Triggers the Necrotrophic Phase In Z Tritici?mentioning
confidence: 97%
“…Environmental stresses such as light, water availability and temperature fluctuations may play a role, but the switch may also be linked to pathogen conditions or host developmental signals. Z. tritici probably uses several mechanisms to induce necrosis, including the production of protein effectors (Brunner et al, 2013;Gohari et al, 2015;Keon et al, 2007;Rudd et al, 2008;Rudd et al, 2015). In fact, several genes encoding small cysteine rich proteins are highly expressed during the necrotrophic phase.…”
Section: What Triggers the Necrotrophic Phase In Z Tritici?mentioning
confidence: 99%
“…Here, we identified 12 secreted cysteine-rich proteins (3-10 cysteine residues) of which nine were small secreted proteins (SSPs) (less than 300 amino acids, Mirzadi Gohari et al, 2015). Several SSPs have shown to exhibit effector functions in various pathosystems (Rep, 2005;Houterman et al, 2007;Bolton et al, 2008).…”
Section: Fungal Secreted Proteinsmentioning
confidence: 97%